A Challenge in Diagnosis of Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome (TB-IRIS) - Suryana K (Dove Medical Press, 2020)
Ketut Suryana Department of Internal Medicine, Merpati Clinic, HIV and Allergy - Clinical Immunology Services Unit, Wangaya Hospital, Denpasar, Bali, IndonesiaCorrespondence: Ketut SuryanaDepartment of Internal Medicine; Merpati Clinic; HIV and Allergy - Clinical Immunology Services Unit, Wangaya Hospital, Akasia Street, VIII No. 22, Denpasar, Bali 80235, IndonesiaTel +628 5953783944Email ketutsuryana@gmail.comAbstract: Tuberculosis immune reconstitution inflammatory syndrome (TB-IRIS) in HIV-infected patients is the sign and symptom of exacerbation, or radiological manifestation of Mycobacterium tuberculosis (Mtb) infection, can describe the improvement of the immune system after initiating highly active antiretroviral therapy (HAART). No approved or explicit symptomatic tests for TB-IRIS exist, the diagnosis depends on the clinical manifestations. Here we report a TB-IRIS case with diagnostic challenges.Keywords: HIV infection, tuberculosis, HAART, TB-IRIS, diagnostic challenge